Pengaruh Perak Merah (Pemberian Ekstrak Melia Azedarach atau daun Mindi) Terhadap Tekanan Darah Tikus Putih Galur Wistar (Ratus Norvegicus) Yang diinduksi DOCA-Salt (Deoxycorticosterone acetate) - Bartimeus Nicomama Hutabarat (Program Studi Farmasi UNAJA, 2025)
Hypertension is a major degenerative disease and one of the leading causes of global morbidity and mortality. This study aimed to evaluate the effect of Melia azedarach (perak merah) leaf extract on blood pressure in DOCA-salt-induced hypertensive Wistar rats (Rattus norvegicus). The study was conducted at the Laboratory of Universitas Adiwangsa Jambi using a post-test only control group design. Rats were divided into five groups: normal, hypertensive (DOCA-salt), and three treatment groups receiving graded doses of Melia azedarach leaf extract. The results showed that the extract significantly reduced both systolic and diastolic blood pressure compared to the hypertensive control group (p < 0.05). The most pronounced antihypertensive effect was observed at the intermediate dose, indicating an optimal pharmacological response at this level. These findings suggest the potential of Melia azedarach as a natural antihypertensive agent, supporting its role in the development of complementary therapies for hypertension.